1996
DOI: 10.1097/00006123-199601000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative Activity and Invasiveness among Pituitary Adenomas and Carcinomas: An Analysis Using the MIB-1 Antibody

Abstract: Although histologically benign, one-third of all pituitary tumors will be invasive of surrounding structures. In this study, the relationship between the proliferative activity in pituitary adenomas and their invasiveness was investigated. Invasion was defined as gross, operatively or radiologically apparent infiltration of dura or bone. Using the recently developed MIB-1 monoclonal antibody, which recognizes the Ki-67 cell cycle-specific nuclear antigen, the growth fractions of 37 noninvasive adenomas, 33 inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
251
4
11

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 408 publications
(291 citation statements)
references
References 17 publications
22
251
4
11
Order By: Relevance
“…Other studies confirmed the validity of comparative results with all antibodies cited (24). Since 1995, studies evaluating the MIB-1 monoclonal antibody in pituitary tumors have been reported in the literature (11,12,(25)(26)(27)(28)(29)(30)(31)(32)(33). In the studies by Knosp et al (15), Zhao et al (33) and Mastronardi et al (12), the mean positive reaction to Ki-67 was 1.1, 1.4, and 2.64%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies confirmed the validity of comparative results with all antibodies cited (24). Since 1995, studies evaluating the MIB-1 monoclonal antibody in pituitary tumors have been reported in the literature (11,12,(25)(26)(27)(28)(29)(30)(31)(32)(33). In the studies by Knosp et al (15), Zhao et al (33) and Mastronardi et al (12), the mean positive reaction to Ki-67 was 1.1, 1.4, and 2.64%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have shown a correlation between cell proliferation marker expression and tumor aggressiveness, pituitary tumors generally grow slowly. 26,48 The lack of significant correlation between COX-2 expression and the presence of distant metastasis in pituitary tumors is not surprising. Similar results were reported with respect to colorectal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Details of immunohistochemistry, including the duration of exposure and control procedures for these three stains, as well as the morphometric quantification method have been described in previous publications. 25,26,32,33 Most tumors (n ϭ 119) were fixed in glutaraldehyde, routinely processed, embedded in Epon-Araldite, and studied by transmission electron microscopy.…”
Section: Morphologic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some adenomas, however, grow rapidly despite their benign histologic features and invade the cavernous sinus (2,3). The histopathologic findings often do not predict the biologic behavior of these atypical tumors (4,5).…”
mentioning
confidence: 99%